2015
DOI: 10.1007/s00442-015-3476-2
|View full text |Cite
|
Sign up to set email alerts
|

Top predators affect the composition of naive protist communities, but only in their early-successional stage

Abstract: from two non-naive and two naive sites, which are climatically similar. We then conducted a common-garden experiment, with and without the presence of the top predator, in which we recorded changes in community composition, body size spectra, bacterial density, and respiration. We found that the top predator had no statistical effect on global measures of community structure and functioning. However, it significantly altered protist composition, but only in naive, early-succession communities, highlighting tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 75 publications
(105 reference statements)
1
21
0
Order By: Relevance
“…However, bacterivore protozoans of similar phenotype, size, and of the same genus (e.g., Colpoda , Colpidium, Bodo ) as those in North America have established within the leaves of the introduced S. purpurea (Fragnière ; Zander et al. ). These characteristics enabled us to use functionally similar Swiss and North American protozoan communities in our experiment.…”
Section: Methodsmentioning
confidence: 99%
“…However, bacterivore protozoans of similar phenotype, size, and of the same genus (e.g., Colpoda , Colpidium, Bodo ) as those in North America have established within the leaves of the introduced S. purpurea (Fragnière ; Zander et al. ). These characteristics enabled us to use functionally similar Swiss and North American protozoan communities in our experiment.…”
Section: Methodsmentioning
confidence: 99%
“…All samples from all sites remained cooled for the same amount of time (48 h) before initiating the experiments in order to slow biotic interactions and to avoid overheating during transportation. This procedure allowed all treatments to experience the same initial conditions and is a common practice used in Sarracenia research (Paisie et al , Zander et al ). Water from all five sites was filtered with a large, sterilized mesh size (2 mm) to remove the midge ( Metriocnemus knabi ) and flesh fly larvae ( Fletcherimyia fletcheri ), and detritus, in order to create homogenized nutrient availability in each of the five communities.…”
Section: Methodsmentioning
confidence: 99%
“…Bacterial density was then standardized across sites by adjusting the volume of the communities with autoclaved deionized water, resulting in 1.09 × 10 7 bacteria per ml for each origin. This technique is standard for research conducted on the Sarracenia system, as it has been shown that the members of the food web are able to easily survive and maintain normal interactions, even when placed directly into deionized water (Kneitel and Miller , Hoekman , Gray , Kadowaki et al , Kneitel , Zander et al ). As a control, an equal volume of water from each of the five sites was also pooled to make the ‘mixed origin’ community.…”
Section: Methodsmentioning
confidence: 99%
“…While Adlassnig et al. () detected Sarcophagidae larvae inside European populations of congeneric Sarracenia flava ; other researchers did not find arthropod inquilines living inside the pitchers during their studies (Gebühr et al., ; Zander, Bersier, & Gray, ; Zander et al., ). The presence of insect inquilines, which are able to leave the pitcher after metamorphosis, seems to be unresolved in the European populations.…”
Section: Discussionmentioning
confidence: 93%
“…A final possible source of Dipteran DNA could be from the pollinators of S. purpurea (Jürgens, Sciligo, Witt, El‐Sayed, & Suckling, ), as it is possible that our metabarcoding approach detects Dipteran DNA which has been transferred during these visits. Although the particular inquiline and prey species differ between native and allochthonous populations, invertebrate functional groups may be important biological predictors of pitcher plant range, as inquiline successional stages are thought to be similar in pattern (Gray, Akob, Green, & Kostka, ; Zander et al., ).…”
Section: Discussionmentioning
confidence: 99%